Evaluation of reactivity indexes and durability properties of slag-based geopolymer concrete incorporating corn cob ash. (20th October 2020) - Oyebisi, Solomon; Ede, Anthony; Olutoge, Festus; Ogbiye, Samuel
Highlights: The activity indexes of GGBFS-CCA blends increase as CaO, MgO, and Al2 O3 increase. Pozzolanic activity of GGBFS-CCA blends increases as SiO2 and Al2 O3 increase. AIs significantly correlate with the compressive strength of GGBFS-CCA GPC. GGBFS-CCA GPC offers a better resistance to sulfate attacks. Abstract: The method of determining the quantities of geopolymer concrete (GPC) ingredients to attain the required and specifiable characteristics is complex owing to the involvement of more variables compared with Portland cement concrete (PCC) systems. Therefore, this study evaluated the hydraulic responses and chemical resistance of GPC produced with supplementary cementitious materials (SCMs), ground granulated blast furnace slag (GGBFS) and corn cob ash (CCA) at ambient curing conditions. Corn cob was dehydroxylated at 600 °C and used as a partial replacement for GGBFS at 0, 20, 40, 60, 80, and 100%. The activators used were 12, 14 and 16 M concentration (M) of both sodium silicate (SS) and sodium hydroxide (SH). The chemical compositions of individual and mixed binders were analyzed, while the chemical moduli of each and blended binder were examined and evaluated based on the significant reactive oxides, hence resulting in the evaluation of reactivity indexes (RIs). Moreover, the compressive strength was predicted based on the RIs and mix design proportions (MDPs) of the blended concrete, while the durability properties of each concrete sample were investigated. The results indicated that the oxide compositions of GGBFS and CCA influenced the compressive strength of GPC produced. Compared with the experimental results, the predictive compressive strengths based on the RIs and the MDPs yielded a high precision with 95% "R 2 ". Furthermore, the incorporation of both GGBFS and CCA increased the durability of GPC produced against sulfate attacks. Ultimately, the model equations developed by this study can be beneficial in the refinement of mix designs of both GPC and conventional concrete incorporating SCMs provided the oxide compositions of the elements are obtained.